2018
DOI: 10.18535/ijsrm/v6i6.mp01
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Need for Family Planning Among Women of Reproductive Age in Plateau State Nigeria

Abstract: Abstract:Family planning provides individuals and couples the ability to adequately space each pregnancy. Contraceptive uptake is still low in developing countries. This study aims to determine the proportion of women with unmet need for family planning in plateau State. Methods and materials: This was a cross sectional study, employing quantitative and qualitative data collection techniques. Multistage sampling technique was used to select 300 study participants across the three senatorial zones in Plateau St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…This study showed that the proportion of birth protected against neonatal tetanus among mothers who gave birth within six month found to be 58.57% which is in line with study done in Peshawar district Pakistan and Northern Ethiopia about 55.6% and 56.2% respectively (12,25) and it is somewhat higher than study conducted in different community of Nigeria (24%) (14) and study conducted in 2016…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This study showed that the proportion of birth protected against neonatal tetanus among mothers who gave birth within six month found to be 58.57% which is in line with study done in Peshawar district Pakistan and Northern Ethiopia about 55.6% and 56.2% respectively (12,25) and it is somewhat higher than study conducted in different community of Nigeria (24%) (14) and study conducted in 2016…”
Section: Discussionsupporting
confidence: 86%
“…The study, which was conducted in a selected community in Nigeria, revealed that less than half of the respondents, or 24%, had been protected against neonatal tetanus during their previous pregnancy; nearly 88.6% had ever received one dose of tetanus vaccine (14), and 4.6% had never received any dose of tetanus vaccine in Cameroon (15). multilevel analysis conducted in demographic health survey of 10 east African country showed that 50.4% of rural women was protected against neonatal tetanus (16) and another study in Kenya showed that 90.5% of mothers received a second dose of tetanus vaccine during their pregnancy (17).…”
mentioning
confidence: 99%
“…We categorized the independent variables into individual and community factors. Individual factors recoded included woman's age (15-24, 25-34, and 35-49); level of education (no education, primary, secondary/higher); wealth index (poor, middle and rich); working status (working and not working); number of living children (0-1, 2-3, 4-5, 6+); husband's desire for children (Both want the same number of children, husband wants more, husbands wants few, don't know); decision-maker on a woman's health care (this is based on a question in the DHS that asks a person who usually decides on respondent's health care) and this was categorized as All women interviewed aged 15-49 years (62,538) Burundi (17,269), Rwanda (13,497), Tanzania (13,266), Uganda (18,506) Unmarried women (26,341) Burundi (7,487), Rwanda (6,515) Tanzania (5,056), Uganda (7,283) All married women (36,197) Burundi (9,782), Rwanda (6,982) Tanzania (8,210), Uganda (11,223) All sexually active and fecund Married women (32,945) Burundi (8,767), Rwanda (6,472), Tanzania (7,417), Uganda (10,288) Infecund married women (3,253) Burundi (1,015), Rwanda (510) Tanzania (793), Uganda (935) husband/partner alone, respondent alone, joint decision and others; history of child death (yes or no); access to family planning messages (this was measured using four questions that required whether a woman was exposed to family planning messages on radio, television, newspapers and phone in the last month). All the responses to these questions were merged and coded 0 for no exposure to all the media and 1 for those who heard FP messages from any of the four sources.…”
Section: Variables and Their Measurementsmentioning
confidence: 99%
“…Different studies on unmet need have been done in several developing countries like: Ghana [11], Ethiopia [12], Nigeria [13], Cameroon [14], Burundi [15], Kenya [16] and Uganda [17].…”
Section: Introductionmentioning
confidence: 99%
“…The study, which was conducted in a selected community in Nigeria, revealed that less than half of the respondents, or 24%, had been protected against neonatal tetanus during their previous pregnancy; nearly 88.6% had ever received one dose of tetanus vaccine (14), and 4.6% had never received any dose of tetanus vaccine in Cameroon (15). multilevel analysis conducted in demographic health survey of 10 east African country showed that 50.4% of rural women was protected against neonatal tetanus (16) and…”
mentioning
confidence: 99%